The Value Chain of Moringa oleifera Plant and the Process of Producing Its Biodiesel in Ghana - Mohammed Takase; Paul Kwame Essandoh; Richard Kwadzo Asare; Kizzie-Hayford Nazir (The Scientific World Journal)
Moringa oleifera grows well in different parts of Africa, including Ghana, and throughout the world as it can tolerate moderate cold and severe drought. Dubbed as the “Miracle Tree,” Moringa has a number of nutritional, pharmaceutical, and cosmetic applications. It is also used as a cure for diabetes and various forms of cancer. Another promising use of this plant is the production of biodiesel. However, such application demands vast cultivation areas and this can lead to competition with the cultivation of crops for food, forestry, and environmental protection. Furthermore, it requires suitable cultivation schedules that favor the growth of pods containing oil-rich seeds. The present work investigates the availability of land for Moringa cultivation in Ghana to increase the energy production from the plant. The study reports on an overview of the soil, water, and climatic conditions that favor Moringa oleifera cultivation and oil production, the conversion of Moringa oleifera oil to biodiesel, and the performance of Moringa oleifera biodiesel versus mineral diesel as well as the commercial enhancement of the Moringa product.